Given function :[tex]f(x) = 2x^3 + x^2-3x + 1[/tex].
We need to find the average rate of change from x = −2 to x = 0.
Let us find the values of y-coordinates for x=-2 and x=0 for the given function on the graph.
[tex]f(-2) = 2(-2)^3 +(-2)^2-3(-2) + 1=-5[/tex]
[tex]f(0)=\:2\left(0\right)^3\:+\left(0\right)^2-3\left(0\right)\:+\:1 =1[/tex]
Formula for average rate of change is :
[tex]f_{avg}=\frac{f(b)-f(a)}{b-a}[/tex]
Plugging the values of f(a), f(b), a and b in the above formula, we get
[tex]f_{avg}=\frac{0-(-5)}{0-(-2)} = \frac{5}{2}[/tex].